(untitled) (Research, Society and Development, 2020)
An organic fertilizer that is increasingly gaining ground in agriculture is bokashi. Bokashi is the result of a composting method based on the addition of a liquid solution of effective microorganisms, which are anaerobic bacteria and lactic acid yeasts. A technique from Japan that was adapted to Brazil in the late 1980s by Japanese immigrants. In Brazil, it is known as "Fermento da Vida", for bringing life to the soil, increasing the number and diversity of microorganisms that live in it. It is noted that the scientific knowledge about bokashi has not been explored much, besides, there is no bibliographical research on this organic fertilizer. In this context, the objective of this research was to systematize the studies carried out on bokashi in the areas of agriculture and biological sciences, environmental science, biochemistry, genetics and molecular biology, immunology and microbiology, chemical engineering, energy, multidisciplinary, chemistry, social and veterinary sciences. The present work was carried out using the research instrument Periódico Capes, through the Scopus and Web Of Science (WOS) databases. For both bases, the following keywords were used: bokashi; to download the searched documents, the EndNote X7 Software was used. The survey was conducted on July 1, 2019. Through this review survey, it can be concluded that more than 50% of the articles published on bokashi in the last 20 years of research are focused on the area of ​​agriculture and biological sciences and sciences environmental, demonstrating that other areas such as veterinary, social sciences, chemistry, multidisciplinary, energy, chemical engineering, immunology and microbiology, biochemistry, genetics and molecular biology, are scarce in research related to fertilizer.